Association Between ROX Index and Outcomes of High Flow Nasal Cannula in Post-extubated Patients - Srichareonchai, Thiti; Songrin, Metanee (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: High flow nasal cannula (HFNC) therapy is widely used in post-extubated patients. However, no standard parameter is available to predict the outcomes of HFNC during the post-extubated period. The ratio of oxygen saturation (ROX) index is used to predict HFNC failure in acute hypoxemic respiratory failure patients but there is insufficient evidence for use in post-extubated period. Objectives: To evaluate ROX index as a parameter to anticipate outcomes of HFNC in post-extubated patients. Methods: Cross-sectional study by Retrospective chart review was performed to investigate the role of ROX index in predicting outcomes of HFNC in post-extubated patients, i.e., successful extubation, 28 - day and hospital mortality, hospital length of stay (LOS). Baseline characteristics, respiratory and hemodynamic data were collected 6 hours before; and 2 - 6 hours, 6 - 12 hours, and 12 - 24 hours after HFNC application, subsequently the ROC analysis was performed. Results: Of 236 patients, 196 (83%) and 40 (17%) succeeded and failed extubation after HFNC use respectively.At 6 - 12 hours of HFNC use, the mean ± SD of ROX indices forsucceeded and failed groups were 12.66 ± 1.89 and 6.71 ± 1.44 (breath/min)-1, respectively and the ROX index cut-off value of 9.4 (breath/min)-1 (AUROC = 0.991, 95% CI = 0.980-1.000) was strongly associated with successful extubation of HFNC application during post-extubated period. Higher ROX index at 2 - 6 hours of HFNC was associated with lower 28-day and hospital mortality, and shorter hospital LOS. Conclusions: ROX index can be a tool to predict outcomes of HFNC use in post-extubation period, with ROX index 9.4 (breath/min)-1 at 6 - 12 hours of HFNC use associated with successful extubation.